Reproductive rights in India: the search for a 'new' constitutional home - Pillai, G (2022)
Reproductive rights remain deeply contested. Their scope, the duties they impose on the State, their response to conflicting interests, and in some cases their very protection within constitutions are being fiercely debated globally. In India, reproductive rights are not enumerated constitutionally. The Thesis seeks to construct the appropriate constitutional home for reproductive rights in India, to both anchor these rights within the Constitution and define their contours.